Functional genetic screening and therapeutic targeting of recurrent glioblastoma - Chokshi, Chirayu R (My University, 2022)
Glioblastoma (GBM) remains the most aggressive and prevalent malignant primary brain tumor in adults. Unchanged since 2005, standard of care (SoC) consists of surgical resection, followed by radiation therapy (RT) with concurrent and adjuvant chemotherapy with temozolomide (TMZ). Despite these therapeutic efforts, patients succumb to recurrent disease with a median overall survival of 14.6 months and a five-year survival rate of 5.5-6.8%. Therapeutic failure is largely explained by ITH and the presence of treatment-resistant GBM stem-like cells (GSCs). Given the lack of understanding of recurrent GBM and absence of second line therapies patients, I hypothesize that genome-scale functional genetic interrogation will unravel recurrent GBM-specific tumor biology and inform development of novel therapeutics. First, I compared primary and recurrent GBM at the genetic, transcriptomic, proteomic and functional genetic levels. These analyses map a multilayered genetic response to drive tumor recurrence, identifying protein tyrosine phosphatase 4A2 (PTP4A2) as a novel modulator of self-renewal, proliferation and tumorigenicity at GBM recurrence. Mechanistically, genetic perturbation and a small molecule inhibitor of PTP4A2 repress axon guidance activity through a dephosphorylation axis with roundabout guidance receptor 1 (ROBO1) and exploit a genetic dependency on ROBO signaling. Importantly, engineered anti-ROBO1 single-domain antibodies also mimic the effects of PTP4A2 inhibition. Given the genetic dependency on ROBO signaling and enrichment of ROBO1 expression in GBM tissues, I undertook a campaign to evaluate ROBO1 as a therapeutic target in recurrent GBM and develop anti-ROBO1 chimeric antigen receptor T (CAR-T) cells using camelid single-domain antibodies targeting human ROBO1. I optimized the design of anti-ROBO1 CAR-T cells and tested the anti-tumor activity of these modalities in in vitro using patient-derived recurrent GBM lines and orthotopic patient-derived xenograft models. I present data to expand the repertoire of GBM-enriched antigens suitable for effective CAR-T cell therapy. Given that resistance to SoC and disease relapse are inevitable for GBM patients, pre-clinical and clinical advancement of immunotherapeutic modalities, combined with recent insights into the tumor immune microenvironment, are poised to improve clinical outcomes for this patient population.
Keywords: Glioblastoma; Tumor relapse; CRISPR; Chimeric antigen receptor; Immunotherapy; Functional genomics; Patient-derived models